Magma Pressure-Temperature-Time Paths During Mafic Explosive Eruptions - Newcombe, Megan E.; Plank, Terry; Zhang, Youxue; Holycross, Megan; Barth, Anna; Lloyd, Alexander S.; Ferguson, David; Houghton, Bruce F.; Hauri, Erik (Frontiers in Earth Science, 2020)
We have constrained syneruptive pressure-temperature-time (P-T-t) paths of mafic magmas using a combination of short-timescale cooling and decompression chronometers. Recent work has shown that the thermal histories of crystals in the last few seconds to hours of eruption can be constrained using concentration gradients of MgO inside olivine-hosted melt inclusions, produced in response to syneruptive cooling and crystallization of olivine on the inclusion walls. We have applied this technique to the 1974 subplinian eruption of Fuego volcano; the 1977 fire-fountain eruption of Seguam volcano; and three eruptions of Kilauea volcano. Of the eruptions studied so far, melt inclusions from the 1959 Kilauea Iki eruption record the highest syneruptive cooling rates (3 – 11 °C/s) and the shortest cooling durations (4 – 19 s), while inclusions from the 1974 Fuego eruption record the slowest cooling rates (0.1 – 1.7 °C/s) and longest cooling durations (21 – 368 s). The high cooling rates inferred for the Kilauea Iki and Seguam fire fountain eruptions are consistent with air quenching over tens of seconds during and after fragmentation and eruption. Melt inclusions sampled from the interiors of small (~6 cm diameter) volcanic bombs at Fuego are found to have cooled more slowly on average than inclusions sampled from ash (with particle diameters <2 mm) during the same eruption, as expected based on conductive cooling models. We find evidence for a systematic relationship between cooling rates and decompression rates of magmas, in which rapidly-ascending gas-bearing magmas experience slower cooling during ascent and eruption than slowly-ascending magmas. Our magma P-T-t constraints for the Kilauea Iki eruption are in broad agreement with isentropic models that show that the dominant driver of cooling in the conduit is adiabatic expansion of a vapor phase; however, at Fuego and Seguam, our results suggest a significant role for latent heat production and/or open-system degassing (both of which violate assumptions required for isentropic ascent). We thereby caution against the application of isentropic conduit models to magmas containing relatively high initial water concentrations (e.g., arc magmas containing ~4 wt% water).